2014
DOI: 10.1016/j.hal.2014.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptome profiling of a harmful algal bloom

Abstract: Metagenomic methods provide a powerful means to investigate complex ecological phenomena. Developed originally for study of Bacteria and Archaea, the application of these methods to eukaryotic microorganisms is yet to be fully realized. Most prior environmental molecular studies of eukaryotes have relied heavily on PCR amplification with eukaryote-specific primers. Here we apply high throughput short-read sequencing of poly-A selected RNA to capture the metatranscriptome of an estuarine dinoflagellate bloom. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Cells of the thecate (“armored”) dinoflagellates Prorocentrum hoffmannianum (NCBI Biosample SAMN03075519) , Prorocentrum minimum (NCBI TSA GBFP01000000, BioSample SAMN02768558; see Cooper et al. ), Prorocentrum micans (NCBI Biosample SAMN03075521), and Prorocentrum sp. (NCBI Biosample SAMN03075526) were disrupted using a 1 min cycle on a Mini‐Beadbeater‐1 (Biospec Products, Bartlesville, OK) while the athecate dinoflagellates Amphidinium carterae (NCBI Biosample SAMN03015296) , and P. glacialis (NCBI Biosample SAMN03075516) were not disrupted using a beadbeater prior to RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Cells of the thecate (“armored”) dinoflagellates Prorocentrum hoffmannianum (NCBI Biosample SAMN03075519) , Prorocentrum minimum (NCBI TSA GBFP01000000, BioSample SAMN02768558; see Cooper et al. ), Prorocentrum micans (NCBI Biosample SAMN03075521), and Prorocentrum sp. (NCBI Biosample SAMN03075526) were disrupted using a 1 min cycle on a Mini‐Beadbeater‐1 (Biospec Products, Bartlesville, OK) while the athecate dinoflagellates Amphidinium carterae (NCBI Biosample SAMN03015296) , and P. glacialis (NCBI Biosample SAMN03075516) were not disrupted using a beadbeater prior to RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The first application of DinoSL in dinoflagellates metatranscriptomics was documented by Lin et al [26]. Since then, a number of studies has been reported regarding metatranscriptomics approaches to elucidate the dynamic nature of species' interactions during HABs and gene expression patterns during bloom development [20,79,80].…”
Section: Habs Dynamicsmentioning
confidence: 99%
“…Primary methods for examining phytoplankton dynamics within water quality monitoring programs typically have used bulk plankton community analyses (for example, chlorophyll a, primary productivity, nutrient uptake rates, etc.). Sequencing of mRNA transcripts from the environment and subsequent analysis of gene expression patterns (commonly referred to as metatranscriptomics) has been shown to be a powerful tool for identifying the distinct cellular-level processes conducted by bloom-forming taxa within the background of all metabolic activities performed within a mixed plankton assemblage (Cooper et al, 2014). Recent applications of metatranscriptomic approaches have provided new insights into microalgal processes in natural marine environments and include characterization of the phytoplankton response to iron enrichment (Marchetti et al, 2012) and resource partitioning among distinct phytoplankton species in nutrient-rich coastal environments (Alexander et al, 2015).…”
Section: Introductionmentioning
confidence: 99%